Enhancing Children's Reading Comprehension And Object Recognition Through Interactive Learning Media - Arifin, Syaadiah; Hafsah, Hafni; Aziz, Firman; Fujiono, Fujiono; Hanayanti, Citra Siwi (Jurnal Scientia, 2024)
The role of interactive learning media in improving reading comprehension and object recognition in children. Using a literature review method, this research explores a range of interactive applications designed to support children's learning. Findings from the studies reviewed show that apps that integrate multimedia elements and interactive features can increase children's motivation and engagement, and improve their cognitive skills. However, there are challenges in ensuring that apps are not only entertaining but also educational, as well as the importance of parental involvement in the use of apps.